2018
DOI: 10.1016/j.gaitpost.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual-motor regulation in locomotor pointing while approaching a curb

Abstract: Locomotor pointing is a task that has been the focus of research in the context of sport (e.g. long jumping and cricket) as well as normal walking. Collectively, these studies have produced a broad understanding of locomotor pointing, but generalizability has been limited to laboratory type tasks and/or tasks with high spatial demands. The current study aimed to generalize previous findings in locomotor pointing to the common daily task of approaching and stepping on to a curb. Sixteen people completed 33 repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…To facilitate comparison of the current study with previous research and to prevent the participants from producing the same stereotypical walk each time, they were required to place one of their early steps onto a target on the ground (a blue anti-slip mat, dimensions: 30 cm long and 150 cm wide), which was placed in 10 different positions ranging from 1 to 2.5 times the a-priori measured step lengths from the start of the walkway [ 7 ]. In addition, a final condition was added in which no early stepping target was presented and the participants completed the task unconstrained.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…To facilitate comparison of the current study with previous research and to prevent the participants from producing the same stereotypical walk each time, they were required to place one of their early steps onto a target on the ground (a blue anti-slip mat, dimensions: 30 cm long and 150 cm wide), which was placed in 10 different positions ranging from 1 to 2.5 times the a-priori measured step lengths from the start of the walkway [ 7 ]. In addition, a final condition was added in which no early stepping target was presented and the participants completed the task unconstrained.…”
Section: Methodsmentioning
confidence: 99%
“…Research has shown that this type of locomotor pointing is made possible through an intimate coupling of perception and action [ 1 6 ]. The regulation required for such a task is not limited to athlete populations, but rather, is also used by members of the general population on a daily basis when performing locomotor pointing tasks, such as approaching and stepping onto a curb [ 7 ]. Whilst these studies would suggest that locomotor pointing is a skill that can be comfortably performed by all humans, research concerning age-related changes in locomotor pointing in otherwise healthy populations is limited.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations